Simulated microgravity triggers epithelial mesenchymal transition in human keratinocytes - Danilo Ranieri (Scientific Reports, 2017)
Abstract The microgravitational environment is known to affect the cellular behaviour inducing modulation of gene expression and enzymatic activities, epigenetic modifications and alterations of the structural organization. Simulated microgravity, obtained in the laboratory setting through the use of a Random Positioning Machine (RPM), represents a well recognized and useful tool for the experimental studies of the cellular adaptations and molecular changes in response to weightlessness. Short exposure of cultured human keratinocytes to the RPM microgravity influences the cellular circadian clock oscillation. Therefore, here we searched for changes on the regenerative ability and response to tissue damage of human epidermal cells through the analysis of the effects of the simulated microgravity on the re-epithelialization phase of the repair and wound healing process. Combining morphological, biochemical and molecular approaches, we found that the simulated microgravity exposure of human keratinocytes promotes a migratory behavior and triggers the epithelial-mesenchymal transition (EMT) through expression of the typical EMT transcription factors and markers, such as Snail1, Snail2 and ZEB2, metalloproteases, mesenchymal adhesion molecules and cytoskeletal components.